Factors determining return migration of Goan emigrants - Gomes, Roy; Chandran, Sarath (Asian Development Policy Review, 2025)
Goa is a small, progressive state in India and a former Portuguese colony with a long history of international migration, experiencing return migration in recent periods. The study attempts to locate the significant factors causing the return migration of Goans into the State. The study uses primary data collected from 400 return migrants on twenty-two attributes responsible for their return. An Exploratory Factor Analysis (EFA) is used to determine the factors responsible for return migration and compare them against their socioeconomic attributes. The EFA identifies six factors for return migration, namely, Workplace (W), Personal (P), Job-related (JR), Friends (F), Family (FA), and Facilities (FC). Family, Job-related, and Workplace factors are the main factors causing return migration, and international migration has helped them improve their quality of life and standard of living. The government should take proactive steps to utilize the skills and experience acquired by the return migrants by creating an enabling environment in the State and rehabilitating them based on their motivation to return to their home country. The study is significant for formulating the reintegration and rehabilitation policies for the return migrants who have significantly contributed to the State’s economic development.